Blueprint for SingTel in the 21st century. - Mong, Mien Hui. (2008)
The liberalization of the telecom industry means that Singapore is finally experiencing full-fledged competition in the telecom market. Our report tries to come up with strategies for SingTel to be number one in the industry. The strategies will help SingTel to increase market share, profits and to enhance customer’s perception.